HERMENEUTIKA SEBAGAI SISTEM INTERPRETASI PAUL RICOEUR DALAM MEMAHAMI TEKS-TEKS SENI - Abdul Wachid B.S. Wachid B.S. (Imaji, 2006)
Based on hermeneutics’ history, it is known that Paul Ricoeur bringshermeneutics into activities of interpreting and understanding texts (textualexegesis). According to Ricoeur, who is a professor of philosophy at NanterreUniversity, “Basically the whole philosophy is an interpretation tointerpretation.” He agrees with Nietzsche that “Life itself is an interpretation. Ifthere emerges plurality of meanings, interpretation is needed”.To study the hermeneutics of interpretation of Paul Ricoeur, we do notneed to trace its root to the previous growth of this study. Richard E. Palmereven places Ricoeur’s hermeneutics separated from other previous similarstudies, like the hermeneutics of sacred-book interpretation theory, hermeneuticsof philology method, hermeneutics of linguistic understanding, hermeneutics ofhuman science foundation (Geisteswissenschaften), and hermeneutics of daseinphenomenology.Key words: hermeneutics, interpretation and understanding of text